Droplet and Aerosol Suspension Times in Ambient Air in Confined Spaces and Transmission of COVID-19: Influence of Environmental Factors - Islam, M. R.; Naqib, S. H. (Journal of Scientific Research, 2021)
The COVID‑19 pandemic, alternatively known as the coronavirus pandemic, is an unfolding pandemic of coronavirus disease 2019 (COVID‑19) across the entire globe in an unprecedented proportion. COVID-19 is caused by severe acute respiratory syndrome coronavirus 2. The mode of transmission of COVID-19 is a subject of intense research. The airborne transmission is one prime possibility. Breathing and talking are natural processes which generate exhaled particles. The exhaled air is an aerosol/droplet composed of naturally produced particulates of varying size. The duration over which the aerosols/droplets are suspended in the air is an important factor. Long suspended aerosols/droplets are potential source of transmission, particularly in confined spaces. We have calculated times of suspension by considering various environmental factors, namely, the ambient temperature and relative humidity in a confined space, in this work. Both temperature and relative humidity affect the suspension time of the exhaled aerosols/droplets with varying degree. The effects of environmental factors are significant for aerosols, particularly for those with small radii. We have discussed the possible implications of our findings in this paper.